Gianotti-Crosti syndrome in a child following intranasal influenza virus vaccination. - Domingues, E.; Belazarian, L.; Sweeney, S.M. (European Journal of Pediatric Dermatology, 2009)
An eight year old girl was first observed to have a bilaterally symmetric distribution of pruritic and pink papules found to be consistent with Gianotti-Crosti syndrome. There was no evidence of infection, but the patient had received the intranasal influenza vaccination 6 weeks prior to the onset of symptoms.